Effects of karate fights on Achilles tendon stiffness measured by myotonometry - Pozarowszczyk, B.; Pawlaczyk, W.; Smoter, M.; Zarzycki, A.; Mroczek, D.; Kumorek, M.; Witkowski, K.; Kawczynski, A. (Journal of Human Kinetics, 2017)
The aim of the study was to investigate the influence of karate fights on Achilles tendon stiffness in karate competitors. Eleven male karate fighters participated in the present study. A handheld MyotonPRO device (MyotonPRO, Myoton Ltd, Estonia) was applied to measure Achilles tendon stiffness in karate fighters. The Achilles tendon was tested 5 cm above the tuber calcanei. Stiffness measurements were performed before and after eight sparring fights. Each fight lasted 2 min and was separated by a 2 min rest period. Achilles tendon stiffness for the dominant leg increased significantly from before fights (751.57 ± 123.493 N/m) to immediately after fights (809.43 ± 160.425 N/m) (p = 0.012). Presented results should be used by strength and conditioning coaches in training programs as a way to decrease the risk of injury.